BDE-47-mediated cytotoxicity via autophagy blockade in 3D HepaRG spheroids cultured in alginate microcapsules - Miranda, Raul Ghiraldelli; Guarache, Gabriel Cicolin; Leão, Anderson Henrique F.F.; Pereira, Gustavo José; Dorta, Daniel Junqueira [UNESP] (Elsevier, 2024)
Polybrominated Diphenyl Ethers (PBDEs) are a major class of brominated flame retardants, and their widespread use has led them to be considered contaminants with emerging concern. PBDEs have been detected in the indoor air, house dust, food, and all environmental compartments. The congener BDE-47 (2,2′,4,4′-tetrabromodiphenyl ether) is the most prevalent, and hepatotoxicity, neurotoxicity, immunological changes, endocrine disruption, and genotoxic potential have been related to its exposure. Although the BDE-47 molecular toxicity pathway is directly related to intrinsic apoptotic cell death, the role of autophagy in BDE-47 toxicity remains unclear. In this context, three-dimensional cell culture has emerged as a good strategy for the replacement of animals in toxicological testing. Here, we used HepaRG spheroids cultured in alginate microcapsules to investigate the role of autophagy in BDE-47-mediated hepatotoxicity. We developed mature and functional HepaRG spheroids by culturing them in alginate microcapsules. Histological analysis revealed that HepaRG spheroids formed an extracellular matrix and stored glycogen. No apoptotic and/or necrotic cores were observed. BDE-47 showed concentration- and time-dependent cytotoxicity in HepaRG spheroids. In the early exposure period, BDE-47 initially disrupted mitochondrial activity and increased the formation of acid compartments that promoted the increase in autophagic activity; however, this autophagy was blocked, and long-term exposure to BDE-47 promoted efficient apoptotic cell death through autophagy blockade, as evidenced by an increased number of fragmented/condensed nuclei. Therefore, for the first time, we demonstrated BDE-47 toxicity and its cell pathway induces cell death using a three-dimensional liver cell culture, the HepaRG cell line.
Keywords: 3D-HepaRG spheroids; Apoptosis; Autophagy; BDE-47 cytotoxicity